Clonostachys rosea: Production by Submerged Culture and Bioactivity Against Sclerotinia sclerotiorum and Bemisia tabaci - Mascarin, Gabriel Moura; da Silva, Ana Vitória Reina; da Silva, Thiago Pereira; Kobori, Nilce Naomi; Morandi, Marcelo Augusto Boechat; Bettiol, Wagner (Frontiers in Microbiology, 2022)
Among the prospective biocontrol agents, the saprophytic filamentous fungus Clonostachys rosea is an excellent necrothrophic mycoparasite of numerous plant pathogenic fungi. However, its commercial development has been hampered by mass production difficulties during solid-state fermentation. Conversely, submerged liquid fermentation shortens the cultivation time while increasing yields of fungal propagules. However, this method has been overlooked for C. rosea. In this work, we investigated the impact of liquid pre-culture inoculum to a two-stage fermentation process using rice grains and compared it to the traditional solid-state fermentation. In parallel, we studied the submerged cultivation of C. rosea by manipulating carbon-to-nitrogen (C:N) ratio and nitrogen source, with further optimization of spore production in a benchtop bioreactor. Additional bioassays included assessing the bioactivity of water-dispersible microgranules (containing submerged conidia) against the whitefly (Bemisia tabaci biotype B) and Sclerotinia sclerotiorum (causal agent of white mold). Our results showed a maximum concentration of 1.1 × 109 conidia/g-dry-matter after 7 days of cultivation by two-stage fermentation process. Liquid fermentation delivered 1.4 × 109 submerged conidia/mL after 7 days with 50:1 C:N ratio, and it also induced the production of microsclerotia (MS) up to 1.35 × 104/mL in 6 days with 10:1 C:N, both media were supplemented with dextrose monohydrate and soybean meal. Fermentation batches carried out in a benchtop bioreactor with medium 50:1 C:N ratio and amended with soybean meal rendered a production peak on the 4th day, corresponding to 1.11 × 109 conidia/mL and 4.35 × 108 CFU/mL. Following air drying, conidia production from surviving C. rosea biomass was estimated at 3.4 × 1010 conidia/g of formulated product. Both submerged conidia and microsclerotia of C. rosea inhibited 100% germination of S. sclerotiorum sclerotia in bioassays. Air-dried submerged conidia exhibited a striking suppressive activity on sclerotia (88% mycoparasitism) and early whitefly nymphs (76.2% mortality) that reflected a LC50 of 3.2 × 104 CFU/g soil and 1.5 × 107 CFU/mL, respectively. Therefore, liquid culturing C. rosea may offer a feasible and cost-effective method for its large-scale production, alleviating critical constraints to their commercial use while providing an additional tool for management of B. tabaci and S. sclerotiorum.